FACTORS RELATED TO GIVING HBO IMMUNIZATION TO INFANTS AT UJUNG PADANG HEALTH CENTER - Nurmala (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
According to the International Task Force on Hepatitis-B Immunization, Indonesia is included in the moderate and high endemic group of hepatitis B, with a prevalence in the population of 7% -10%. At least 3.9% of Indonesian pregnant women are people with hepatitis with a risk of maternal transmission of approximately 45%. Currently it is estimated that there are more than 11 million people with Hepatitis-B in Indonesia. In countries with a low prevalence of hepatitis B, most people with hepatitis are aged 20-40 years, whereas in countries with a high prevalence of hepatitis B, most people with hepatitis are children. The purpose of this study was to determine the factors related to Hb0 immunization in infants. This type of research is Analytical. The population of this study were all mothers who had babies 0-7 days at the Ujung Padang Health Center from January to August. The sample in the study was 60 people. The results of the study were obtained based on the administration of Hb0 immunization, it was known that the majority of respondents were not given Hb0 immunization as many as 32 respondents (53.3%) and a minority of respondents were given Hb0 immunization as many as 28 respondents (46.7%) and it can be concluded that there is a relationship between education, occupation, number of children, knowledge, birth attendants, delivery assistance places and family support for giving Hb0 immunization to infants. It is hoped that this research can become input for health workers to improve the quality of health services and education as well as information about Hb0 immunization in infants by providing counseling The results of the study were obtained based on the administration of Hb0 immunization, it was known that the majority of respondents were not given Hb0 immunization as many as 32 respondents (53.3%) and a minority of respondents were given Hb0 immunization as many as 28 respondents (46.7%) and it can be concluded that there is a relationship between education, occupation, number of children, knowledge, birth attendants, delivery assistance places and family support for giving Hb0 immunization to infants. It is hoped that this research can become input for health workers to improve the quality of health services and education as well as information about Hb0 immunization in infants by providing counseling The results of the study were obtained based on the administration of Hb0 immunization, it was known that the majority of respondents were not given Hb0 immunization as many as 32 respondents (53.3%) and a minority of respondents were given Hb0 immunization as many as 28 respondents (46.7%) and it can be concluded that there is a relationship between education, occupation, number of children, knowledge, birth attendants, delivery assistance places and family support for giving Hb0 immunization to infants. It is hoped that this research can become input for health workers to improve the quality of health services and education as well as information about Hb0 immunization in infants by providing counseling place for delivery assistance and family support for giving Hb0 immunization to infants. It is hoped that this research can become input for health workers to improve the quality of health services and education as well as information about Hb0 immunization in infants by providing counseling place for delivery assistance and family support for giving Hb0 immunization to infants. It is hoped that this research can become input for health workers to improve the quality of health services and education as well as information about Hb0 immunization in infants by providing counseling.